PENGARUH PERPUTARAN KAS DAN PIUTANG TERHADAP ROA PADA KOPERASI SIMPAN PINJAM MITRA USAHA DESA CISEMPUR - Suhaendang Nurjaya; istikomah istikomah; Asep Iwa Hidayat (Jurnal Riset Akuntansi Politala, 2023)
It is certain that to carry out its activities each cooperative requires a certain amount of funds, both funds originating from loans and own capital. This study aims to determine the effect of Cash Turnover and Accounts Receivable Turnover on Return On Assets (ROA) in the Cisempur Village Mitra Savings and Loans Cooperative. The method used in this research is multiple linear regression analysis method. The type of data used is secondary data obtained from the Cisempur Village Partner Savings and Loans Cooperative with a total sample of 60 data for 5 years. Based on the results of the regression test in this study, it shows that cash turnover has no significant effect on Return On Assets (ROA) in the Cisempur Village Mitra Savings and Loans Cooperative. Accounts Receivable Turnover has no significant effect on Return On Assets (ROA) in Cisempur Village Business Partner Savings and Loans Cooperative. Cash Turnover and Accounts Receivable Turnover have no significant effect on Return On Assets (ROA) in the Cisempur Village Business Partner Savings and Loans Cooperative.